Analisis Harga Cryptocurrency, Total Cryptocurrency, Jumlah Transaksi Cryptocurrency Terhadap Keputusan Investasi Aset Cryptocurrency - Kristiawan, Muhammad Rio; Lilianti, Emma; Putra, Andri Eko (Jurnal Media Akuntansi (Mediasi), 2025)
ABSTRACT This study aims to examine the effect of cryptocurrency prices, total cryptocurrencies, number of cryptocurrency transactions on cryptocurrency asset investment decisions. This study is a quantitative study that has the aim of testing data and presenting answers to various problem formulations regarding the effect of cryptocurrency prices, total cryptocurrencies, the number of cryptocurrency transactions on cryptocurrency asset investment decisions. The sample used in this research is 56 time-series data with a period of one last year, obtained by purposive sampling method. The data used is secondary data obtained through the website https://www.coinmarketcap.com and the data is processed using a software called E-views with data analysis techniques using the Ordinary Least Squarer (OLS) and Error Correction Model (ECM) procedures. The results of this study show that the cryptocurrency price variable, total cryptocurrency, the number of cryptocurrency transactions are significantly positive on cryptocurrency asset investment decisions. Keywords: Aset cryptocurrency, Ethereum, Cryptocurrency. ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh harga cryptocurrency, total cryptocurrency, dan jumlah transaksi cryptocurrency terhadap keputusan investasi pada aset crypto. Penelitian ini merupakan studi kuantitatif yang bertujuan untuk menguji data dan memberikan jawaban atas berbagai pertanyaan mengenai dampak harga cryptocurrency, total cryptocurrency, dan jumlah transaksi cryptocurrency terhadap keputusan investasi pada aset crypto. Sampel yang digunakan dalam penelitian ini terdiri dari data, 56 data time series selama satu tahun yang diperoleh dengan metode sampling bertarget. Data yang digunakan adalah data sekunder yang diperoleh dari website https://www.coinmarketcap.com, data dianalisis menggunakan software bernama E-Views dan Ordinary Least Squares (OLS) Teknik analisis data menggunakan metode dan model koreksi kesalahan (ECM) digunakan telah diproses. Hasil penelitian ini menunjukkan bahwa variabel harga cryptocurrency, total cryptocurrency, dan jumlah transaksi cryptocurrency berpengaruh positif signifikan terhadap keputusan investasi pada aset cryptocurrency. Kata kunci: Cryptocurrency Aset, Ethereum, Cryptocurrency.